Application of hyperspectral indices for the detection of grass cover changes from spectrometric survey data - Lyalko, V. I.; Shportiuk, Z. M.; Sibirtseva, O. M.; Dugin, S. S. (Reports of the National Academy of Sciences of Ukraine, 2014)
The vegetation indices, i. e. the red edge position (REP) and the MERIS terrestrial chlorophyll index (TCI) obtained from the annual terrestrial spectrometry measurements for grass cover at three points of observation for the test sites within the Mariinsky park, "Dynamo" stadium, and the Dnieper riverbank in the Kyiv city for the period from 2009 to 2013 are studied. The most wide region of shifts from the mean values of these two indices are indicated for grass cover on the Dnieper riverbank, the narrowest one is detected for the "Dynamo" stadium grass lawn. The relationship between REP and TCI values with the correlation coefficient r = 0.95 is determined. The prognostic edicted linear regression model for REP versus TCI relation (R2 = 0.45, n = 14) with the index of agreement d = 0.98 is developed. The model validation is performed using spectrometric data on 06.06.2013.